2017
DOI: 10.24188/recia.v9.n1.2017.495
|View full text |Cite
|
Sign up to set email alerts
|

Recursos florales usados por dos especies de Bombus en un fragmento de bosque subandino (Pamplonita-Colombia)

Abstract: ResumenSe presentan los resultados de un análisis palinológico en dos especies del género Bombus en cercanías de Pamplonita (Norte de Santander-Colombia) durante los meses de abril y mayo de 2010. A partir de muestras coprológicas se identificaron y contaron un total de 1585 granos, dentro de los cuales Solanaceae, Asteraceae, Malvaceae y Fabaceae fueron los taxa mas abundantes. En términos de diversidad, en abril se encontraron los valores más altos con respecto a los tipos de polen para ambas especies, aunqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The Protected Forest Reserve Serranía de Coraza is located in the north of Colombia, in the Caribbean plains, in the Department of Sucre over the Montes de María [32] (Figure 1). Coraza shows temperatures ranging between 25 and 28 • C and precipitation between 896 and 1233 mm per year.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The Protected Forest Reserve Serranía de Coraza is located in the north of Colombia, in the Caribbean plains, in the Department of Sucre over the Montes de María [32] (Figure 1). Coraza shows temperatures ranging between 25 and 28 • C and precipitation between 896 and 1233 mm per year.…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, there is a dry seasonal period from November to February where rainfall decreases to less than 200 mm. The average relative humidity is 83.5% [32,34].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Anthers are poricidal and require sonication to release the pollen (Buchmann and Cane, 1989). Palynological identification of pollen provisions have shown that lulo pollen is collected by Bombus pullatus, Bombus atratus (Mercado et al, 2017), and Euglossa nigropilosa (Otero et al, 2014). Greenhouse experiments demonstrated the efficient use of commercial colonies of Bombus atratus (Almanza, 2007), and Bombus terrestris (Messinger et al, 2016) as pollinators but there is no information on the wild pollinator community.…”
Section: Study Systemmentioning
confidence: 99%
“…Thus, it is common to observe some degree of overlap in the food sources they collect, particularly when food becomes scarce, like during the rainy season. Actually, it has been observed that despite the existence of an extensive diversity of oral resources available in a given area, bees concentrate their efforts on some of them (Cauich et al 2004;Azmi et al 2017; Mercado et al 2017), perhaps due to an innate preference for small owers with radial symmetry, open corollas or short tubes, in which the access to food is relatively easy (Ramalho 2004). To evaluate the degree of food niche overlap among meliponine it is necessary to know the identity of the plants they collect food from, which is normally achieved by palynological analysis, that helps in identifying the origin of the pollen grains in pollen or honey samples (Eltz et al 2001).…”
Section: Introductionmentioning
confidence: 99%